An empirical study of the Mexican banking system's network and its implications for systemic risk - Serafín Martínez-Jaramillo; Biliana Alexandrova-Kabadjova; Bernardo Bravo-Benítez; Juan Pablo Solórzano-Margain (Banco de México, 2012)
With the purpose of measuring and monitoring systemic risk, some topological properties of the interbank exposures and the payments system networks are studied. We propose non-topological measures which are useful to describe the individual behavior of banks in both networks. The evolution of such networks is also studied and some important conclusions from the systemic risks perspective are drawn. A unified measure of interconnectedness is also created. The main findings of this study are: the payments system network is strongly connected in contrast to the interbank exposures network; the type of exposures and payment size reveal different roles played by banks; behavior of banks in the exposures network changed considerably after Lehmans failure; interconnectedness of a bank, estimated by the unified measure, is not necessarily related with its assets size.
Keywords: C01; C02; C44; C63; G21; 330; systemic risk; financial networks; payment systems; Geldmarkt; Zahlungsverkehr; Finanzsektor; Bank; Mexiko